The Chilean education reform and its impact on quality. An economic vision - Icochea, Olympia (1993)
The author studies Chile's educational reforms in the eighties, and assesses their successes and failures in terms of quality of teaching. The reforms rested principally on two aspects: decentralized administration (municipal authorities assuming responsibility) and the application of market economic mechanisms for financing schools. Chile's democratic government subsequently added a number of measures that the reforms lacked, such as increasing outlay to the sector and improving educational quality in subsidized schools. However, the success of these reforms is still uncertain.